Cover Feature: A DNA‐Encoded Library of Chemical Compounds Based on Common Scaffolding Structures Reveals the Impact of Ligand Geometry on Protein Recognition (ChemMedChem 13/2018). (6th July 2018) - Favalli, Nicholas; Biendl, Stefan; Hartmann, Marco; Piazzi, Jacopo; Sladojevich, Filippo; Gräslund, Susanne; Brown, Peter J.; Näreoja, Katja; Schüler, Herwig; Scheuermann, Jörg; Franzini, Raphael; Neri, Dario
Abstract : The Cover Feature shows the affinity capture of small organic compounds encoded by a DNA fragment, serving as amplifiable identification barcode. The technology enabled the discovery of a nanomolar ligand for human tankyrase‐1 (TNKS1), starting from an encoded combinatorial library which featured seven different central scaffolds, functionalized with two sets of chemical building blocks. More information can be found in the Communication by Nicholas Favalli, Raphael Franzini, Dario Neri et al. onpage 1303 in Issue 13, 2018 (DOI:10.1002/cmdc.201800193 ).